IMPLEMENTATION OF BASIC COMPETENCIES IN SURVEYING TECHNIQUES AT SMK CONSTRUCTION AND PROPERTY ENGINEERING EXPERTISE PROGRAMS - Muhammad Haristo Rahman; Tuti Iriani; Irika Widiasanti (LPPM Universitas Negeri Jakarta, 2023)
This study aims to obtain complete information about the implementation Of Education Process Standards at SMK Construction and Property Engineering Expertise Programs in Jakarta. Research related to how Implementation of Learning Land measurement engineering subjects to achieve the expected competency in accordance with the established basic competencies, and what factors are done by the teacher to achieve the competence of Surveying Techniques. This research is intended in a qualitative descriptive study. The data source was obtained from interviews with the deputy headmaster of the curriculum section and the teacher of the subject of Surveying Techniques as well as the basic competency documents and the Learning Implementation Plan (RPP). Data collection procedures carried out by observation, in-depth interviews, and documentation. The analysis is done by describing and interpreting the data from interviews and documentation studies and checking the validity of the data is done by triangulation. From the results of research conducted the implementation of the standard process in learning Surveying Techniques goes well by paying attention to predetermined standards namely planning, implementation and assessment by attention to the cognitive, affective, and psychomotor elements of students.